2018
DOI: 10.1097/pas.0000000000001084
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Immunohistochemistry Assay Concordance in Urothelial Carcinoma of the Bladder and Hypopharyngeal Squamous Cell Carcinoma

Abstract: Programmed death ligand-1 (PD-L1) immunohistochemistry is used to guide treatment decisions regarding the use of checkpoint immunotherapy in the management of urothelial carcinoma of the bladder and hypopharyngeal (HP) squamous cell carcinoma. With increasing PD-L1 testing options, a need has arisen to assess the analytical comparability of diagnostic assays in order to develop a more sustainable testing strategy. Using tissue microarrays, PD-L1 expression in tumor cells (TCs) and immune cells (ICs) was manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
64
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 38 publications
10
64
4
2
Order By: Relevance
“…In addition, the expression of PD-L1 could be slightly lower than the expression reported in other studies, as differences in the percentage of positive cells have been described for different anti PD-L1 antibody clones. 42 In conclusion, the BCG response in high-risk NMIBC patients is associated with local and systemic immune alterations in the bladder tissue prior to BCG treatment. Our results suggest the potential predictive value of the combined assessment of peritumoral Th1/Th2 polarization and peripheral immunity composition for the identification of individuals who will obtain more benefit from BCG treatment.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the expression of PD-L1 could be slightly lower than the expression reported in other studies, as differences in the percentage of positive cells have been described for different anti PD-L1 antibody clones. 42 In conclusion, the BCG response in high-risk NMIBC patients is associated with local and systemic immune alterations in the bladder tissue prior to BCG treatment. Our results suggest the potential predictive value of the combined assessment of peritumoral Th1/Th2 polarization and peripheral immunity composition for the identification of individuals who will obtain more benefit from BCG treatment.…”
Section: Discussionmentioning
confidence: 89%
“…Two recent studies investigated the concordance of different PD‐L1 assays in urothelial cancer tissue microarrays, and found PD‐L1 expression in 12–29% of samples . Tretiakova et al .…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Two recent studies investigated the concordance of different PD-L1 assays in urothelial cancer tissue microarrays, and found PD-L1 expression in 12-29% of samples. 11,12 Tretiakova et al found concordant PD-L1 assay outcome in matched primary urothelial carcinoma and lymph node metastasis in 90%. 12 This number is slightly higher than the rate of 77-82% in our series, and can be explained by the fact that they used PD-L1 assays taking tumour cell expression into account, while the SP142 scoring algorithm is based on immune cell expression only.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of PD-L1 in cancer cells results in anergy of T lymphocytes (by targeting PD-1 on their surface); this way, tumor cells escape destruction by the immune system and maintain a subverted immune-suppressive tumor microenvironment [27,28]. It has become routine, then, for pathology departments to assess PD-L1 expression by immunohistochemistry in BlCa tissue specimens [29,30].…”
Section: Immune Therapies-brief Overview In Bladder Cancermentioning
confidence: 99%